The Greeks and hedging explained - Leoni, Peter; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
A practical guide to basic and intermediate hedging techniques for traders, structerers and risk management quants. This book fills a gap for a technical but not impenetrable guide to hedging options, and the'Greek' (Theta, Vega, Rho and Lambda) -parameters that represent the sensitivity of derivatives prices.
Keywords: Science